2002
DOI: 10.1086/338000
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NF‐κB Activation by Infection withToxoplasma gondii

Abstract: The interaction of host cells with microbial products or their invasion by pathogens frequently results in activation of the NF-kappaB family of transcription factors. The studies presented here reveal that in vivo, infection with Toxoplasma gondii results in the activation of NF-kappaB. To determine whether host cells could activate NF-kappaB in response to invasion by T. gondii, Western blots, immunofluorescence, and electrophoretic mobility shift assays were used to assess the response of host cells to infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
113
4
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 48 publications
10
113
4
1
Order By: Relevance
“…However, despite the initiation of NF-B signaling, infection with T. gondii did not lead to the activation of NF-B but to its termination. The reason for disabling NF-B is associated with blocking of p65 translocation to the nucleus (10,12,13). Other studies have demonstrated that T. gondii activates NF-B, which up-regulates the expression of anti-apoptotic genes to facilitate the replication of the pathogen (15)(16)(17).…”
mentioning
confidence: 99%
“…However, despite the initiation of NF-B signaling, infection with T. gondii did not lead to the activation of NF-B but to its termination. The reason for disabling NF-B is associated with blocking of p65 translocation to the nucleus (10,12,13). Other studies have demonstrated that T. gondii activates NF-B, which up-regulates the expression of anti-apoptotic genes to facilitate the replication of the pathogen (15)(16)(17).…”
mentioning
confidence: 99%
“…This observation demonstrated the importance of NF-κB p65 component as a key factor in the protection of the infected fibroblast against apoptosis [99]. It should be noted, however, that movement of NF-κB to the nucleus is not observed in all types of infected cells including macrophages, which do not exhibit NF-κB translocation early after invasion [105][106][107]. This may be due to inherent differences between cell types or a result of examining translocation at different time points post-invasion.…”
Section: Role Of the Nf-κb Pathwaymentioning
confidence: 86%
“…Experiments performed with protein kinase inhibitors suggest that the synthesis of TNF␣, induced by soluble antigen of T. gondii, is protein kinase C-dependent, whereas the kinase does not appear to play a dominant role in soluble antigeninduced IL-12 and IL-10 responses, arguing that distinct parasite signals are involved in monokine induction (14). In vivo infection of mice with virulent or avirulent strains of T. gondii leads to activation of NF-B in peritoneal cells (37). In contrast, Butcher and Denkers (19) have no evidence for NF-B p65 translocation in peritoneal cells of mice infected in vivo with a virulent strain of T. gondii.…”
Section: Discussionmentioning
confidence: 98%